Strategic design under uncertain evaluations: Structural analysis of design-build auctions - Hidenori Takahashi (University of Mannheim, Department of Economics, 2015)
I investigate firms' competition over price and product design under uncertain design evaluations in the context of Design-Build (DB) auctions. Reviewers' design evaluations contain uncertainty from a bidder's perspective, leading luck to curtail differences in firms' chances of winning. I model bidders' behavior and derive semiparametric identification of the model primitives. Uncertain evaluations worsen the expected price of design quality, and exacerbate an auctioneer's uncertainty in auction outcomes. A simple adjustment in the auction mechanism may completely shut down the impact of uncertain evaluations on bidding incentives, restoring efficient allocations of projects.
urn:nbn:de:bsz:180-madoc-388821
Keywords: 330